Why were FIFA World Cup Tickets so cheap? Monopoly Pricing, Demand Quality and Two-Sided Markets - Christoph Eichhorn; Marco Sahm (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
We examine the pricing decision of a multi-product monopolist in a two-sided market where the type structure of buyers on one side of the market is an important determinant of profit on the other side. In this situation it might be optimal to set prices below the maximum sellout price and to ration demand by a random mechanism in the first market to reach a type distribution more favorable for sales in the other market. The model establishes demand quality as an alternative link between markets in addition to standard quantitative effects and explains frequently observed underpricing, e.g. in the (sports) entertainment industry. It also provides an explanation for the effort a monopolist incurs to deter from resale.
urn:nbn:de:bvb:19-epub-1357-8
Keywords: L12; D42; D45; 330; Underpricing; Demand Rationing; Resale Deterrence; Fußballsport; Großveranstaltung; Preiselastizität; Monopolistischer Wettbewerb; Theorie